Antipsychotics-induced hyperprolactinemia and screening for macroprolactin - Bakliza, Ana; Filipcic, Igor; Grosic, Vladimir; Ivezic, Ena; Matic, Katarina; Geres, Natko; Vuk Pisk, Sandra; Ruljancic, Nedjeljka (Biochemia Medica, 2021)
Introduction: High prolactin (PRL) concentrations are found in laboratory test results of patients on majority of antipsychotic drugs. Prevalence rates and degrees of severity of hyperprolactinemia (HPRL) based on PRL concentration may depend on the presence of macroprolactin in the serum. The aim of the study was to investigate the difference between PRL concentrations before and after precipitation of macroprolactin and to examine if there were any changes in the categorization of HPRL between samples prior and after precipitation. Materials and methods: Total of 98 female patients (median age 33; range 19-47 years) diagnosed with a psychotic disorder, proscribed antipsychotic drugs, and with HPRL were included. Total PRL concentration and PRL concentration after macroprolactin precipitation with polyethylene glycol (postPEG-PRL) were determined by the chemiluminometric method on the Beckman Coulter Access2 analyser. Results: Total PRL concentrations (median 1471; IQC: 1064-2016 mlU/L) and postPEG-PRL concentrations (median 1453; IQC: 979-1955 mlU/L) were significantly correlated using intraclass correlation coefficient for single measurements (mean estimation 0.96; 95%CI 0.93-0.97) and average measurement (mean estimation 0.98; 95%CI 0.96-0.99), and all investigated female patient had HPRL according to PRL and postPEG-PRL concentration. The median PRL recovery following PEG precipitation was 95; IQC: 90-100%. There was substantial agreement (kappa test = 0.859, 95% CI: 0.764- 0.953) between the categories of HPRL severity based on total PRL concentrations and postPEG-PRL concentrations. Conclusion: The study demonstrated that HPRL was present in all subjects using the reference interval for total PRL concentration and postPEG-PRL concentration with no significant impact of macroprolactin presence in the serum on the categorization of patients according to severity of HPRL.